Kebutuhan, Keserakahan Dan Rendahnya Supremasi Hukum Sebagai Faktor Penentu Perilaku Korupsi Aparatur Pemerintah - Pura, Rahman; Sahidah (STIEM BONGAYA, 2025)
This study aims to analyze the influence of needs, greed and low supremacy of law on corrupt behavior. The study was conducted on government officials in Makassar City. This study used a quantitative survey approach, collecting data from 93 respondents using a structured questionnaire. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings of the study indicate that needs, greed and low supremacy of law have a significant effect on corrupt behavior. The results of this study have important implications for efforts to prevent and overcome corruption. The government and related institutions need to pay attention to the needs of the community, especially economic needs, and provide strict punishment or sanctions for perpetrators of corruption to reduce the possibility of corruption